Revealing the Penumbra through Imaging Elemental Markers of Cellular Metabolism in an Ischemic Stroke Model - Pushie, M.; Crawford, A.; Sylvain, N.; Hou, H.; Hackett, Mark; George, G.; Kelly, M. (American Chemical Society, 2018)
Stroke exacts a heavy financial and economic burden, is a leading cause of death, and is the leading cause of long-term disability in those who survive. The penumbra surrounds the ischemic core of the stroke lesion and is composed of cells that are stressed and vulnerable to death, which is due to an altered metabolic, oxidative, and ionic environment within the penumbra. Without therapeutic intervention, many cells within the penumbra will die and become part of the growing infarct, however, there is hope that appropriate therapies may allow potential recovery of cells within this tissue region, or at least slow the rate of cell death, therefore, slowing the spread of the ischemic infarct and minimizing the extent of tis sue damage. As such, preserving the penumbra to promote functional brain recovery is a central goal in stroke research. While identification of the ischemic infarct, and the infarct/penumbra boundary is relatively trivial using classical histology and microscopy techniques, accurately assessing the penetration of the penumbra zone into undamaged brain tissue, and evaluating the magnitude of chemical alterations in the penumbra, has long been a major challenge to the stroke research field. In this study, we have used synchrotron-based X-ray fluorescence imaging to visualize the elemental changes in undamaged, penumbra, and infarct brain tissue, following ischemic stroke. We have employed a Gaussian mixture model to cluster tissue areas based on their elemental characteristics. The method separates the core of the infarct from healthy tissue, and also demarcates discrete regions encircling the infarct. These regions of interest can be combined with elemental and metabolic data, as well as with conventional histology. The cell populations defined by clustering provide a reproducible means of visualizing the size and extent of the penumbra at the level of the single cell and provide a critically needed tool to track changes in elemental status and penumbra size.